Does US-China Trade War Matter on ASEAN Stock Market: Event-study Approach - Budi Setiawan (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
The trade war between the US and China by imposing tariffs has the potential to affect global financial stability. As the largest economy in the world, the US and China had been trading goods and services globally. Then, when these countries have retaliated, the tariff war will affect the global supply chain, international trade, economy, and the stock market. This research examined the effect of the US-China trade war on ASEAN stock prices using an event-study approach. The result shows that the ASEAN stock market has positive abnormal returns during pre-event period (12%). In contrast, ASEAN stock markets shifted to negative abnormal return (-7.4%) in the short-term window, indicating that the stock market is efficient. Stock price reflects the information from the market quickly. However, the impact of the trade war on the ASEAN stock market is insignificant.